The Influence Of Physical Education On The Physical And Mental Development Of Grade 4 Students At State Elementary School 056427 Adin Tengah - Elisabeth Tampubolon; Gita Rismayani; Friska Silaban; Morina Br Ginting; Fajar Sidik Siregar (Outline Publisher, 2024)
This research aims to analyze the influence of physical education on the physical and mental development of elementary school students. Physical education plays an important role in supporting children's growth and development, both physically and mentally. Through structured and directed physical activity, students can develop motor skills, physical strength and improve general health. Apart from that, participation in physical education also has a positive impact on mental aspects, such as increasing concentration, controlling emotions, and social development. This research uses quantitative methods by collecting data through questionnaires filled out by students and teachers. The results of the analysis show that there is a significant positive correlation between participation in physical education and improvements in students' physical and mental conditions. These findings emphasize the importance of physical education as an integral part of the primary school curriculum to support students' holistic development.